Blowup deseo de una mañana de verano - Redgrave, Vanessa 1937-; Hemmings, David 1941-2003; Miles, Sarah 1941- (Turner Entertainment [u.a.], 2004)
A mod London photographer seems to find something very suspicious in the shots he has taken of a mysterious beauty in a desolate park. (www.imdb.com)
Orig.: GB 1966
Caracteristicas especiales disponibles: Comentario de Peter Brunette, banda sonora, trailers
Nebentitel: Michelangelo Antonioni's "Blow-up"
Keywords: Blow up -- Film; Fotograf; London; Fiktionale Darstellung; DVD-Video